Genetic Markers Associated to Dyslipidemia in HIV-Infected Individuals on HAART - Rosmeri K. Lazzaretti; Aline S. Gasparotto; Marina G. de M. Sassi; Carísi A. Polanczyk; Regina Kuhmmer; Jussara M. Silveira; Rossana P. Basso; Cezar A. T. Pinheiro; Mariângela F. Silveira; Eduardo Sprinz; Vanessa S. Mattevi (The Scientific World Journal)
This study evaluated the impact of 9 single nucleotide polymorphisms (SNPs) in 6 candidate genes (APOB, APOA5, APOE, APOC3, SCAP, and LDLR) over dyslipidemia in HIV-infected patients on stable antiretroviral therapy (ART) with undetectable viral loads. Blood samples were collected from 614 patients at reference services in the cities of Porto Alegre, Pelotas, and Rio Grande in Brazil. The SNPs were genotyped by conventional polymerase chain reaction (PCR) and real-time PCR. The prevalence of dyslipidemia was particularly high among the protease inhibitors-treated patients (79%). APOE (rs429358 and rs7412) genotypes and APOA5 −1131T>C (rs662799) were associated with plasma triglycerides (TG) and low-density-lipoprotein cholesterol levels (LDL-C). The APOA5 −1131T>C (rs662799) and SCAP 2386A>G (rs12487736) polymorphisms were significantly associated with high-density-lipoprotein cholesterol levels. The mean values of the total cholesterol and LDL-C levels were associated with both the APOB SP Ins/Del (rs17240441) and APOB XbaI (rs693) polymorphisms. In conclusion, our data support the importance of genetic factors in the determination of lipid levels in HIV-infected individuals. Due to the relatively high number of carriers of these risk variants, studies to verify treatment implications of genotyping before HAART initiation may be advisable to guide the selection of an appropriate antiretroviral therapy regimen.